INTRODUCTION & SIMULATION OF SAFE TRANSFER TECHNIQUE FOR INJURY VICTIMS TO PMR MEMBERS - Dhina Widayati; laviana Nita Ludyanti; Diana Rachmania; Indri Trilina (STIKES dan AKZI Karya Husada Kediri, 2023)
Transfer techniques in evacuating injured victims play an important role in the successful handling of injured cases. This safe transfer technique action is carried out to move the victim to a more comfortable place with a safe technique for both the victim and helper. In the school community, cases of injury are often found, especially musculoskeletal injuries related to sports subject activities. The purpose of this service activity is to provide an introduction and education to PMR members about the technique of moving victims safely through a simulation strategy. The method of implementing this activity is through counseling and simulation involving 25 students from PMR SMAN 1 Kandangan. The implementation of service activities is carried out in 3 sessions, namely: introduction to injury cases through counseling, introduction to techniques for moving injured victims and simulations of how to move victims safely. The result of the service activity was that there was an increase in the knowledge and ability of youth in moving injured victims using safe techniques, namely from some (50%) in the sufficient category (before the activity) increased to almost all (90%) in the good category. Education with a simulation approach can increase adolescents' understanding of techniques for moving victims safely so that they are able to help injured victims by moving them safely. The eduction method with a simulation approach can be used as a medium for conveying information in the management of injury cases.